Śrīharadattācāryapraṇītāyāḥ Padamañjaryāḥ paryālocanam - Tripāṭhī, Tīrtharāja (Bhāvanā-Prakāśanam, 1981)
Study of a medieval supercommentary on Kāśikā, 7th century commentary on Pāṇini's Aṣṭādhyāyī, Sanskrit grammar, by Vāmana and Jayāditya.